Quality of interaction between the nursing personnel and the informal caregivers of people with memory disorders: A systematic review and metasummary of qualitative studies - Johanna Rannikko; Jenny Paananen; Minna Stolt; Riitta Suhonen (Wiley, 2023)
Abstract Aim To explore the factors that affect the quality of interactions between nursing personnel and the informal caregivers of people with memory disorders. Design Systematic review and metasummary of qualitative empirical research. Methods The literature search targeted studies concerning the professional care interactions between nursing personnel and the informal caregivers of people with progressive memory disorders. The search in PubMed, CINAHL, PsycINFO and Scopus covered records from the earliest possible date up to December 2020. The data were summarised using a qualitative metasummary method. Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) checklist was used to validate the reporting process. Results Ten articles were included. As presented in 33 statements, the factors affecting the quality of interactions were related to (1) expectations, (2) memory disorders, (3) interaction strategies, (4) time and place of interactions and (5) organisational aspects. Meeting the individual interactional needs of informal caregivers is recommended. The results provide guidance for improving the quality of interactions between nursing personnel and informal caregivers.